Guyana : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Guyana. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses recent economic developments, the outlook, and risks for the Czech Republic. The economy has been growing at an exceptionally strong pace. Driven by robust domestic demand, output expanded by 4.2 percent-the highest rate in the central and eastern European region-in 2015. Labor market performance has been strong. Fiscal performance was better than budgeted in 2015. The banking sector is stable, and credit growth continues to strengthen. However, economic activity is expected to slow in 2016. Private consumption will remain robust on the heels of higher disposable income and employment, but the projected slowdown in EU-fund absorption will weigh on growth.